Performance evaluation of gamma-ray radiation and ultraviolet light photocatalytic pretreatments of sargassum algae - Halal, Paul Israel S.D (2013)
Gamma-ray irradiation and ultraviolet (UV) light photocalysis were tested for their efficacy as pretreatments for the enzymatic hydrolysis of Sargassum algae. This was done at acidic, basic and neutral pH levels. Gamma ray irradiation was done at the Philippine Nuclear Research Institute Cobalt-60 Multipurpose Irradiation Facility. The dosage was a 100 kilogray cumulative dose done for seven days. In the UV photocalysis pretreatment, the algae solution was exposed to an 18/-watt UV lamp with a 1:10 catalyst to cellulose ration for twenty-four hours. Enzymatic hydrolysis was done for twenty-four hours using cellulose from Trichoderma reesei in a shaking incubator at 50˚C and 150 rpm. Sampling was done every four hours. Results show that gamma pretreatment at neutral pH increases the yield of hydrolysis by 152.94% when compared to untreated samples. This pretreatment is comparable to an autoclave pretreatment in which percentage difference was 4.51%. Ultraviolet light photocalysis increased the yield of enzymatic hydrolysis. The neutral UV pretreatment increased the yield by 49.8% when compared to the untreated samples. The computed energy cost for gamma and UV pretreatment was 0.79 kJ/mg and 14.29 kJ/mg respectively.